Methylation profile of the testes of the flatfish Solea senegalensis - Daniel Ramírez; María Esther Rodríguez; Robert Mukiibi; Carolina Peñaloza; Helena D’Cotta; Diego Robledo; Laureana Rebordinos (Aquaculture Reports)
In aquaculture production, fish phenotypes are influenced by a combination of external and internal factors, while the underlying mechanisms often involve distinct DNA methylation patterns. These play a fundamental role in regulating gene expression in response to environmental shifts. The Senegalese sole (Solea senegalensis) holds significant potential in aquaculture due to its high commercial importance. However, its production faces several challenges, including the inability of F1 soles to reproduce. In our study, we analysed the methylation patterns in the testicular DNA of 12 male S. senegalensis individuals from four distinct groups, which differed in rearing origins (wild and F1 soles) and sexual maturity stages (mature and immature). We employed reduced representation bisulfite sequencing to identify significant methylation differences among studied groups. The differential methylation analysis showed a substantial disparity between the F1 and wild groups. This difference was evident in both the number of different methylated CpGs (DMCpGs) and methylation levels, highlighting a distinction in groups reared under different conditions. The comparison between immature and mature wild groups revealed notable differences, suggesting that the testes methylation profile undergoes few changes in wild individuals during sexual maturity. These differences in methylation between wild and hatchery-born and reared offspring imply epigenetic modifications triggered by rearing in captivity and by the absence of natural stimuli such as temperature fluctuations. We further annotated the DMCpGs based on their position and co-localization with genes in the Senegalese sole genome. Our analysis revealed that the methylation differences observed in DMCpGs were more pronounced in intron regions, with higher methylation levels. Conversely, the methylation differences in exon and promoter areas were more subtle. Upon annotation, we discovered that these DMCpG sites were located near or within various transcription factors. Our comprehensive analysis sheds light on the intricate methylation profile of S. senegalensis, focusing on genes associated with reproductive traits, particularly those related to sex determination (SD) systems and spermatogenesis. Overall, we observe a trend toward higher methylation levels in DMCpGs when comparing F1 individuals to wild groups, as well as immature to mature wild groups. Hence, sexual maturity and place of origin resulted in marked methylation differences, which could potentially affect the expressions of genes involved in both development and reproduction of farmed males. This analysis explores the gene-regulating effects of this epigenetic mechanism providing valuable insights into the variations in methylation found in the testes of Senegalese sole.